Characterization of nanocrystalline anatase titania: an in situ HTXRD study - Jagtap, Neelam; Bhagwat, Mahesh; Awati, Preeti; Ramaswamy, Veda (Thermochimica Acta, 2005)
Nanocrystalline titania was synthesized by the hydrolysis of titanium iso-propoxide using ultrasonication. The powder XRD patterns of the sample were recorded in static air and vacuum using a Philips X-pert Pro diffractometer equipped with a high-temperature attachment (HTK16) from room temperature (298 K) to 1173 K and were analyzed by the Rietveld refinement technique. The anatase to rutile phase transformation was observed at 1173 K for the data collected in static air. Only 3% of anatase titania transformed to rutile when the experiments were carried out at H 73 K in vacuum. The phase transformation from anatase to rutile is accompanied by a continuous increase in the crystallite size of the anatase phase from 9 nm at room temperature to 28 nm at 873 K and then to 50 nm at 1173 K in air while the process of crystallite growth was suppressed in vacuum. A linear increase in the unit cell parameters `a' and `c', and thus, an overall linear increase in the unit cell volume was observed as a function of temperature in static air as well as vacuum. The lattice and volume thermal expansion coefficients (TEC), alpha(a), alpha(c), and alpha(v) at 873 K are 8.57 x 10(-6), 8.71 x 10(-6) and 25.91 x 10(-6) K-1 in air and 18.01 x 10(-6), 14.95 x 10(-6) and 51.13 x 10(-6) K-1 in vacuum, respectively. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: Anatase; HTXRD; Rietveld refinement; rutile; thermal expansion coefficient; titania

Disordered brownmillerite Ba2InCeO5+delta with enhanced oxygen reduction activity - Jijil, Chamundi P.; Unni, SreeKuttan M.; Sreekumar, Kurungot; Devi, R. Nandini (Chemistry of Materials, 2012)
A disordered brownmillerite, Ba2InCeO5+delta, with slight tetragonal distortion from ideal cubic perovskite is synthesized and its oxygen reduction reactivity tested. The material displayed oxygen reduction behavior in alkaline solution comparable to that of standard 40 wt % Pt/C catalyst and attractive activity characteristics which renders it a potential system for low temperature fuel cell applications.
Keywords: brownmillerite; fuel cell; oxygen reduction reaction; Rietveld refinement

Effect of b site coordination environment in the ORR activity in disordered brownmillerites Ba2In2-xCexO5+delta - Jijil, Chamundi P.; Bhange, Siddheshwar N.; Kurungot, Sreekumar; Devi, R. Nandini (ACS Applied Materials & Interfaces, 2015)
Ba2In2O5 brownmillerites in which the In site is progressively doped with Ce exhibit excellent oxygen reduction activity under alkaline conditions. Ce doping leads to structural changes advantageous for the reaction. Twenty-five percent doping retains the ordered structure of brownmillerite with alternate layers of tetrahedra and octahedra, whereas further increase in Ce concentration creates disorder. Structures with disordered oxygen atoms/vacancies are found to be better oxygen reduction reaction catalysts probably aided by isotropic ionic conduction, and Ba2In0.5Ce1.5O5+delta is the most active. This enhanced activity is correlated to the more symmetric Ce site coordination environment in this compound. Stoichiometric perovskite BaCeO3 with the highest concentration of Ce shows very poor activity emphasizing the importance of oxygen vacancies, which facilitate O-2 adsorption, in tandem with catalytic sites in oxygen reduction reactions.
Keywords: brownmillerite; fuel cell; oxygen disorder; oxygen reduction reaction; Rietveld refinement